Distinguishing between human and animal sources of fecal pollution in waters: a review. (9th February 2009) - Tyagi, Punam; Edwards, D.R.; Coyne, M.S.
This review paper discusses some of the earlier and current methods used to identify the human and non-human sources of fecal pollution in water. It is mainly focused on chemical approaches, i.e., fecal sterol and bile acid biomarkers, to identify the sources of fecal pollution. Findings of our study are in agreement with earlier investigations, that it is unlikely for any single determinant to be useful in all situations but a multiple biomarker approach or statistical analysis of microbial and chemical determinants offer the possibility of identifying and apportioning human and animal fecal inputs to natural waters.